Quality variation and biosynthesis of anti-inflammatory compounds for Capparis spinosa based on the metabolome and transcriptome analysis - Liu, Xiaoying; Aimaier, Alimu; Wang, Weilan; Dong, Yuliang; Han, Peng; He, Jiang; Mu, Lihong; Wang, Xinhui; Li, Jinyao (Frontiers in Plant Science, 2023)
Capparis spinosa L. fruits as edible and medicinal plant, has anti-inflammatory activities. The different morphological characteristics of C. spinosa fruits from Yili, Turpan, and Karamay may affect their anti-inflammatory components and functions. In the study, we found that the 95% ethanol extracts (CSE) from the three districts showed remarkable anti-inflammatory effects in vivo and in vitro. However, CSE from Yili fruits significantly reduced CD86 levels on DCs. As a result of metabolomic analysis, the metabolic profiles of the fruits from Yili differed significantly from those of two other districts, which were consistent with transcriptome analysis. 15 compounds with anti-inflammatory activity were screened, and the accumulation of flavonoids was higher in the Turpan and Karamay districts, among which phenolic compounds were the key anti-inflammatory components in C. spinosa. In conclusion, there were significant differences in the morphology, metabolites, transcriptional levels, and anti-inflammatory activity of C. spinosa from the three districts.